2015
DOI: 10.2147/cia.s75945
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative effect of Hachimijiogan, a Japanese herbal medicine, in C2C12 skeletal muscle cells

Abstract: BackgroundHachimijiogan (HJG), Ba-Wei-Di-Huang-Wan in Chinese, is one of the most popular herbal medicines in Japanese Kampo. HJG is often prescribed for the prevention and treatment of age-related diseases. Muscle atrophy plays an important role in aging-related disabilities such as sarcopenia. The purpose of this study was to investigate the possible beneficial effect of HJG on skeletal muscle.MethodsCells of murine skeletal muscle myoblast cell line C2C12 were used as an in vitro model of muscle cell prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Go-sha-jinki-Gan, a traditional Japanese herbal medicine, reduced the loss of skeletal muscle mass and ameliorated the increase in slow skeletal muscle fibers in senescence-accelerated mice (SAMP8) [110]. In an in vitro model of muscle cell proliferation using murine skeletal muscle myoblast cell line C2C12, hachimijiogan (HJG), a Japanese herbal medicine, significantly increased C2C12 cell number when compared to control [111]. Treatment of old mice with Jaeumganghwa-Tang, a traditional herbal formula composed of 12 medicinal herbs, improved muscle strength, increased skeletal muscle mass, and alleviated muscle damage [112].…”
Section: Body Compositionmentioning
confidence: 99%
“…Go-sha-jinki-Gan, a traditional Japanese herbal medicine, reduced the loss of skeletal muscle mass and ameliorated the increase in slow skeletal muscle fibers in senescence-accelerated mice (SAMP8) [110]. In an in vitro model of muscle cell proliferation using murine skeletal muscle myoblast cell line C2C12, hachimijiogan (HJG), a Japanese herbal medicine, significantly increased C2C12 cell number when compared to control [111]. Treatment of old mice with Jaeumganghwa-Tang, a traditional herbal formula composed of 12 medicinal herbs, improved muscle strength, increased skeletal muscle mass, and alleviated muscle damage [112].…”
Section: Body Compositionmentioning
confidence: 99%
“…(D) Untreated Model . In the studies using the untreated C2C12 myoblast model, Takeda et al showed that administration of Hachimijiogan (HJG) to untreated C2C12 cells promoted muscle cell proliferation through activation of ERK1/2 signaling pathway without affecting the Akt signaling pathway [43]. In a study by Sung BK et al, the expression levels of myogenic proteins (MyoD and myogenin) and functional myosin heavy chain (MyHC) were measured to evaluate the myogenic potential of loquat leaf extract (LE).…”
Section: Resultsmentioning
confidence: 99%
“…Broussonetia kazinoki ( B . kazinoki ), Corydalis turtschaninovii , and Hachimijiogan, in vitro, promote myogenic differentiation through activation of key promyogenic kinase (p38 MAPK) or ERK1/2 and MyoD transcription activities (MyoD family transcription factors play a key role in promoting myoblast differentiation) without affecting the Akt signaling pathway [ 13 15 ]. Another in vitro study, performed by Poussard et al, indicated Oligopin, a pine bark extract, as natural antioxidant; in fact, with aging, oxidative stress produces disruption of cytoskeleton and phosphorylated heat-shock protein beta-1 (HSPB1) may help to repair injured structures.…”
Section: Resultsmentioning
confidence: 99%